Investor Protection and Capital Fragility: Evidence from Hedge Funds around the World. (2nd June 2020) - Aragon, George O; Nanda, Vikram; Zhao, Haibei
Abstract: We find that capital flows to hedge funds in different countries are influenced by the strength and the enforcement of investor protection laws. Hedge funds located in weak investor protection countries exhibit greater sensitivity of investor outflow to poor performance, relative to funds in countries with strong protection. Furthermore, weak investor protection is associated with fund managers engaging in greater returns management. Our findings suggest that in countries with weaker investor protection, poor fund performance exposes investors to a greater risk of fraud and legal jeopardy, thus triggering a larger outflow of capital.